Clinical profile of granulomatous mastitis at a tertiary care Hospital Kashmir - Refut Arah Banoo, Altaf Hussain Kambay , Awhad Mueed Yousuf, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Chronic granulomatous mastitis(CGM) is a rare benign inflammatory breastentity characterized by lobulo-centricgranulomas. The nonspecific manifestationsand varied demographic features of thiscondition, as well as similarities in presentationwith other breast conditions, pose substantialdiagnostic and treatment challenges (1). Aim: the study was aimed to evaluate differentclinical presentations and treatment approachesfor granulomatous mastitis in resource limitedsetting.